2015
DOI: 10.1080/17533015.2015.1061570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of creative museum outreach sessions on measures of confidence, sociability and well-being for mental health and addiction recovery service-users

Abstract: Background: The study examined the effects of museum outreach sessions on confidence, sociability and wellbeing measures for mental health (n=85) and addiction recovery (n=59) service-users taking an asset-based approach and research design. Method: Both groups participated in weekly outreach sessions combining object handling and museum visits with arts and craft activities. Using mixed methods, measures of confidence, sociability and wellbeing were evaluated quantitatively through a 'ladder of change' model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
(33 reference statements)
2
26
1
Order By: Relevance
“… [ 130 ] Moon et al, 2000; ( n = 609); US 7th grade students Resiliency perspective focuses on enhancing those factors thought to protect against or reduce substance use (Norman, 1995). [ 181 ] Morse et al, 2015; ( n = 59); UK Art program for addiction recovery service users [ 110 ] O’Donnell et al, 2002; ( n = 2600); US Students (6th, 8th, 10th grade) exposed to community violence Resilience defined as the ability to cope effectively with stress and to exhibit an unusual degree of psychological strength for one’s age and set of circumstances Werner, 1984). The definition has been expanded in newer studies to include successful coping in specific domains, including both behavioural and emotional arenas (Luthar 1991, 1993; Luthar and Zigler 1991).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… [ 130 ] Moon et al, 2000; ( n = 609); US 7th grade students Resiliency perspective focuses on enhancing those factors thought to protect against or reduce substance use (Norman, 1995). [ 181 ] Morse et al, 2015; ( n = 59); UK Art program for addiction recovery service users [ 110 ] O’Donnell et al, 2002; ( n = 2600); US Students (6th, 8th, 10th grade) exposed to community violence Resilience defined as the ability to cope effectively with stress and to exhibit an unusual degree of psychological strength for one’s age and set of circumstances Werner, 1984). The definition has been expanded in newer studies to include successful coping in specific domains, including both behavioural and emotional arenas (Luthar 1991, 1993; Luthar and Zigler 1991).…”
Section: Resultsmentioning
confidence: 99%
“…The key to a more holistic and contextualized approach to resilience research may be to provide equal attention to external protective factors (e.g., social support, family assistance, community programs, enculturation), and consider the mechanisms and interactions between the individual and their potential resources through which resilience can be built/maintained [ 108 , 143 , 146 ]. In fact, resilience-based recovery programs and interventions, focusing on both internal strengths (e.g., confidence, inner spirit, pride, creativity, developing new skills) and external resources (e.g., community supports, social interaction, cultural participation, aftercare), are currently being developed and evaluated [ 102 , 143 , 170 , 172 , 181 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has included studies of active cultural engagement (such as singing, dancing or doing artistic activities) [13][14][15] and receptive cultural engagement (such as visiting museums and galleries). 16,17 However, to date, much of this research has centred on the impact of cultural engagement on recovery for people with depression or on depressive symptomatology in the general population. There remains little research into whether cultural engagement can itself act as a risk-reducing factor for the development of depression, and therefore play a preventative role.…”
Section: Cultural Engagement and Mental Healthmentioning
confidence: 99%
“…Social exclusion has been well researched in relation to mental illness [16,17]. Although arts activities have been found to reduce these feelings [18][19][20] it is possible that such feelings could act as an initial barrier to engagement. This is certainly suggested by studies focusing specifically on depression-related stigma when engaging in arts activities, which have shown that individuals with poor mental health report perceived barriers to arts engagement, such as a fear of being patronised [21].…”
Section: Introductionmentioning
confidence: 99%